Intermittent fasting positively modulates human gut microbial diversity and ameliorates blood lipid profile - Khan, Muhammad Nadeem; Khan, Sidra Irshad; Rana, Madeeha Ilyas; Ayyaz, Arshad; Khan, Muhammad Yousaf; Imran, Muhammad (Frontiers in Microbiology, 2022)
Aim The aim was to evaluate the impact of intermittent fasting (IF) on human body mass index (BMI) and serum lipid profile thorough constructive rectification of gut microbiota. Methods and results Fourteen healthy women and thirty-one men were included in the study. Their blood and fecal samples were collected before and at the end of the study. Blood parameters, anthropometric values, and gut microbiology were noted to investigate the impact of intermittent fasting (IF) on human gut microbiota and physiology. Our data revealed that IF reduces the body weight and improves blood lipid profile, such as increasing high-density lipoprotein (HDL) and decreasing total cholesterol, triglycerides, and low- and very low-density lipoprotein levels. IF also decreases culturable aerobic bacterial count and increased fungal count. It was also found that the gut metagenome is altered considerably after IF. The human fecal bacterial diversity exhibited significant changes in decreased overall bacterial population, increased bacterial diversity (alpha diversity), and promoted evenness within the bacterial population at the species level. Anti-inflammatory bacteria Lactobacillus and Bifidobacterium were favorably increased, while pathogenic bacteria were decreased. Conclusion Collectively, these results indicated that IF could improve lipid profile and body weight in humans, and the potential mechanisms might be via regulating gut microbiota. Significance and impact of the study We demonstrated for the first time that IF improved body weight and blood lipid profile, indicating that IF could mitigate gut microbiota in humans.